Three-Dimensional In Situ Stress Distribution in a Fault Fracture Reservoir, Linnan Sag, Bohai Bay Basin - Jiageng Liu; Yanzhong Wang; Jing Li; Xiaoyu Meng; Jiayi Teng; Zhicheng Wang; Mingzhi Li; Rui Zhu (Journal of Marine Science and Engineering)
The fault fracture body, consisting of faults, fracture zones, cracks, and the matrix, plays a crucial role in controlling oil and gas accumulation. Understanding its spatial distribution and analyzing the in situ stress field are essential for optimizing well design and fracturing operations. This study integrates geological, logging, and seismic data, and employs advanced techniques such as ant tracking to establish a skeletal model of the fault fracture body. Reverse modeling and optimization reconstruction are used to construct a three-dimensional geomechanical model of the fracture system. Machine learning techniques, specifically a back propagation (BP) neural network, are utilized to invert the boundary conditions of the study area. Finite element numerical simulation software is then applied to model the three-dimensional in situ stress field under coupled flow–solid interaction. The reservoirs in the study area are characterized by a dense structure, low porosity, and low permeability. The results indicate that the maximum horizontal principal stress in the fault fracture reservoir ranges from 68.0 to 72.8 MPa, while the minimum horizontal principal stress ranges from 58.2 to 63.1 MPa. The stress at fractures is lower than that in the surrounding matrix, and stress concentrations occur at both ends of the faults. The in situ stress field exhibits distinct subarea characteristics, with significant stress reductions across fault fractures and directional deflections at faults. These findings provide valuable insights for improving reservoir development efficiency and optimizing well operations in similar geological settings.